Studi Komparatif Portofolio Optimal Menggunakan Proksi LQ 45 dan IHSG Melalui Pendekatan Model Indeks Tunggal - Lestari, Desak Putu Rahayu; Candraningrat, Ica Rika (E-Jurnal Manajemen; Vol 3 No 3 (2014), 2014)
The purpose of this study is to determine the shares of LQ 45 members that form the optimal portfolio when used approach IHSG and LQ 45 Index as a proxy for the market return in the Single Index Model approach and know the differences in average portfolio return, average portfolio risk, and the proportion of shares when used IHSG and LQ 45 Index as a proxy for the market return in the Single Index Model approach. The results show when the IHSG used as a proxy for the market return stocks LQ 45 Index members are elected to form the optimal portfolio the period February 2008 – January 2013 is BBCA (26,64%), BBNI (12,53%), BBRI (5,17%), BMRI (26,82%), dan INDF (28,81%). When used LQ 45 Index as a proxy for the market return stocks LQ 45 members elected the period February 2008 – January 2013 is BBCA (8,23%), BBNI (25,5%), BBRI (3,46%), BMRI (27,58%), INDF (34,23%), dan UNTR (0,97%). The average portfolio return, the average risk of portfolio, and the proportion of shares forming the optimal portfolio with a single index model does not differ significantly when used IHSG and LQ 45 Index as a proxy for the market return.
Keywords: IHSG, LQ 45 Index, Single Index Model, Optimal Portfolio